Differences in direct costs of patients with stage I cutaneous melanoma: A real-world data analysis. Issue 6 (June 2020) - Buja, Alessandra; Rivera, Michele; De Polo, Anna; Zorzi, Manuel; Baracco, Maddalena; Italiano, Irene; Vecchiato, Antonella; Del Fiore, Paolo; Guzzinati, Stefano; Saia, Mario; Baldo, Vincenzo; Rugge, Massimo; et al.
Abstract: Background: Clinical factors, such as tumor thickness, ulceration and growth phase have a role as prognostic factors for stage I melanoma. However, it is still under debate whether these variables influence the related direct costs. We aimed to investigate which clinical factors represent direct health care "cost drivers" for stage I melanoma. Materials and method: Analyses were conducted on a cohort of patients diagnosed with stage I melanoma. Differences in the costs incurred by different groups of patients were examined using Mann-Whitney or Kruskal-Wallis non-parametric tests. Log linear multivariate analysis was used to identify the clinical drivers of the total direct costs one and two years after diagnosis. The study was conducted from the perspective of Italy's National Health care System. Results: One year after diagnosis, patients whose melanomas had a Breslow thickness ≥0.8 mmin (compared with those with lower thickness) and a vertical growth phase (compared with those with radial growth) incurred higher costs for hospitalization, as well as higher overall costs. One year after their diagnosis, treatment of patients with stage I melanoma in the vertical growth phase costs 50% more (95% CI: 22–85%) than their counterparts with a radial growth pattern, resulting in an estimated absolute increase of € 256.23. Having a tumor thicker than 0.8 mm prompted an increase of 91% (95% CI: 43–155%) in the costs (€955.24 in absolute terms). Conclusion: Our data indicate a heterogeneity in the direct costs of stage I melanoma patients during the first year after diagnosis, which can be partly explained by clinical prognostic factors, like tumor thickness and growth pattern.